English Dubbing of Uzbek Films: An Analysis of Current Availability and Future Prospects (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This report analyzes the state of English dubbing for Uzbek cinema, including its current availability, strategic initiatives, and future outlook. While international interest in Uzbek films is increasing and dubbing services are readily available, there is a clear lack of Uzbek films officially dubbed into English for widespread international release. English subtitling remains the main method for making these films accessible to a global audience. Key findings point to a strategy focused on co-productions and film festivals for international reach, the potential of AI dubbing technologies to drive future change, and a domestic dubbing industry that primarily focuses on localizing foreign content into Uzbek.